Factors affecting medication beliefs among patients newly prescribed oral oncolytic agents. Issue 1 (3rd January 2022) - Marshall, Victoria K.; Given, Charles W.; Given, Barbara A.; Lehto, Rebecca H.; Sikorskii, Alla
Abstract: Background: Prescribing oral oncolytic agents (OAs) for advanced cancers is increasing. Aims: To explore changes in medication beliefs and the effects of symptom severity, cognitive effectiveness and depressive symptoms on medication beliefs over 12 weeks. Methods: Secondary analysis of a randomized controlled trial, testing an intervention to promote symptom management and adherence [N = 230]. Questionnaires evaluated medication beliefs, symptom severity, depressive symptoms, and cognitive effectiveness. Linear mixed effects models were used for analyses. Results: OA Necessity beliefs increased over time (mean difference 0.0112, SE = 0.055, p 0.04). Concern beliefs did not change and were lower for advanced cancers (–0.193, SE = 0.067, p < 0.01).Depressive symptoms were related to decreased Necessity beliefs (–0.012, SE = 0.005, p = 0.02), but not Concern beliefs. Medication beliefs were not associated with symptom severity or cognitive effectiveness. Conclusion: Patients with advanced cancer hold different medication beliefs compared to earlier staged cancers, lending insight into potential outcomes beyond adherence.